2002
DOI: 10.4049/jimmunol.168.4.1618
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial-Junctional Adhesion Molecule (VE-JAM)/JAM 2 Interacts with T, NK, and Dendritic Cells Through JAM 3

Abstract: Screening expressed sequence tag databases for endothelial-specific homologs to human junctional adhesion molecule (JAM) and A33-Ag, we identified a protein of 298 aa that represents the recently described vascular endothelial-JAM (VE-JAM)/JAM 2. We confirmed VE-JAM/JAM 2 expression to be restricted to the high endothelial venule of tonsil and lymph nodes, and we further expanded the localization to the endothelium of arterioles in and around inflammatory and tumor foci. In our functional characterizations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
119
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 15 publications
7
119
1
Order By: Relevance
“…Decreased occludin expression, such as seen in both the present and previous studies 72 h post-CFA treatment, will disrupt BBB function (Bolton et al, 1998;Brooks et al, 2005;Brown and Davis, 2005;Hawkins and Davis, 2005;Huber et al, 2002a). Similarly, modulation of JAM-1 protein expression and/or localization is linked to a decrease in normal barrier function, and increased paracellular transport (Dobrogowska and Vorbrodt, 2004;Liang et al, 2002;Mandell and Parkos, 2005). In the present study, we show alterations in the protein expression and localization of occludin, JAM-1 and claudin-5 which correlate to an early (24 h) and a late (72 h) period of increased BBB paracellular permeability to [ 14 C]sucrose.…”
Section: Discussionsupporting
confidence: 56%
“…Decreased occludin expression, such as seen in both the present and previous studies 72 h post-CFA treatment, will disrupt BBB function (Bolton et al, 1998;Brooks et al, 2005;Brown and Davis, 2005;Hawkins and Davis, 2005;Huber et al, 2002a). Similarly, modulation of JAM-1 protein expression and/or localization is linked to a decrease in normal barrier function, and increased paracellular transport (Dobrogowska and Vorbrodt, 2004;Liang et al, 2002;Mandell and Parkos, 2005). In the present study, we show alterations in the protein expression and localization of occludin, JAM-1 and claudin-5 which correlate to an early (24 h) and a late (72 h) period of increased BBB paracellular permeability to [ 14 C]sucrose.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, multiple members of the JAM protein family have also been shown to act as receptors for viruses (Bergelson et al 1997, Barton et al 2001 and have been shown to localize to intercellular junctions (Martin-Padura et al 1998, Liu et al 2000, Cohen et al 2001. The JAM proteins are type I transmembrane proteins consisting of an N-terminal signal peptide, an extracellular domain, a single membrane-spanning domain and a short cytoplasmic tail (Malergue et al 1998, MartinPadura et al 1998, Ozaki et al 1999, Williams et al 1999, Cunningham et al 2000, Liu et al 2000, Palmeri et al 2000, Sobocka et al 2000, Arrate et al 2001, Aurrand-Lions et al 2001a,b, Naik et al 2001, Liang et al 2002, Santoso et al 2002, Hirabayashi et al 2003, Moog-Lutz et al 2003. The extracellular domains of JAMs consist of two immunoglobulin-like loops, each containing an intradomain disulfide bond while the cytoplasmic tails of several members terminate in putative PDZ-binding motifs that appear to mediate binding to intercellular junction-associated scaffold proteins (Cunningham et al 2000, Ebnet et al 2000, 2001, Martinez-Estrada et al 2001, Hamazaki et al 2002, Santoso et al 2002, Hirabayashi et al 2003.…”
Section: The Molecular Basis Of Pmn Transepithelial Migrationmentioning
confidence: 99%
“…The cytoplasmic tail of JAM1 contains a PDZ-binding motif putatively involved in the binding of JAM1 to the cytoplasmic TJ-associated protein ZO-1 (8,9). Three homologs to JAM1 have been reported as follows: JAM-2, which is expressed primarily on endothelial cells (10,11); JAM-3, which is expressed on leukocytes (12)(13)(14); and JAM-4, which was recently reported in kidney and intestinal epithelia (15).…”
mentioning
confidence: 99%